Green synthesized silver nanoparticles by marine endophytic fungus Penicillium polonicum and its antibacterial efficacy against biofilm forming, multidrug-resistant Acinetobacter baumanii. (March 2018) - Neethu, Sahadevan; Midhun, Sebastian Jose; Radhakrishnan, E.K.; Jyothis, Mathew
Abstract: Acinetobacter baumanii, a gram-negative, non-motile, encapsulated coccobacillus which causes infections worldwide. The objective of this study was to find a fungal strain that could be utilized to biosynthesize antibacterial silver nanoparticles (AgNPs) against Acinetobacter baumanii . The present investigation explains rapid and extracellular biosynthesis of silver nanoparticles by the algicolous endophytic fungus, Penicillium polonicum, isolated from the marine green alga Chetomorpha antennina . The obtained silver nanoparticles were characterized by UV-Vis spectroscopy, Raman spectroscopy, Fourier transformation infrared (FTIR), and Transmission electron microscopy (TEM). The SNPs showed a characteristic UV- visible peak at 430 nm with an average size of 10–15 nm. As evident from the FTIR and Raman spectra, possibly the protein components of fungal extract have caused the reduction of silver nitrate. Parametric optimization, including the concentration of AgNO3, ratio of cell filtrate and AgNO3, fungal biomass, reaction time, pH, and presence of light, was done for rapid AgNPs production. The antibacterial efficacy of AgNPs against multi-drug-resistant, biofilm-forming Acinetobacter baumanii, was evaluated by well diffusion assay. The Minimum inhibitory concentration (MIC) of AgNP was 15.62 μgml −1 and the minimum bactericidal concentration (MBC) was 31.24 μgml −1 . Killing kinetic assay revealed complete killing of the bacterial cells within 6 h. Log reduction and percent survival of bacterial cells were analyzed from killing kinetic study. Bactericidal nature of synthesized nanoparticles was confirmed by fluorescent microscopical analysis. The effect of AgNPs on the ultrastructure of bacterial pathogen was evaluated by Transmission electron microscopy. Graphical abstract: Image 1 Highlights: Efficacy of the marine endophytic fungus Penicillium polonicum is proposed. Antibacterial activity of biosynthesized AgNP was studied against biofilm forming multi-drug resistant Acinetobacter baumanii . Mechanism of bactericidal effects of AgNPs demonstrated. Ultra structural studies of nanoparticles-bacterial interactions were explored.